Comparing Returns to Higher Education for School Leavers and Mature Aged students in Australia - Jastrzab, J (My University, 2014)
This paper provides a comparison between the returns to education for those who entered university soon after finishing high school, against those who entered university as ‘mature aged’ students. The motivation stems from the Education literature on the returns to education and adds a more econometrically orientated approach. Firstly, selection models were estimated for the two groups of university entrants using a combination of the Two-step Heckman and Two-Regime approaches, to compare factors that affect the choice of going to university and to account for selection bias. Both models suggest that high school drop outs are highly unlikely to pursue university education. There was no evidence that mature aged students were more likely to come from lower socioeconomic backgrounds; in contrast to previous education studies. Factors such as up-skilling are a more likely explanation. Secondly, the estimated returns between the two groups were compared on the weekly wage earned one, three, five and seven years after graduation. The results show there is a premium for mature aged graduates that dissipates over time. Mature aged graduates earned 47-59% more than their school leaver cohort in the first year after graduation, though this gap is closed between three and five years after graduation. The mature aged may start at a higher point, though the school leavers wage returns continue growing at a faster rate. This evidence reveals that the wage paths of the two groups have different slopes. Future areas of study to consider include the use of a more structurally orientated approach for mapping selection behaviour, and to examine whether there is an ideal point in time for an individual - school leaver or mature aged - to undertake university education.
Keywords: Education and Training -- Tertiary; Learning, education and training; Education and Training; Tertiary; Learning, education and training